2021
DOI: 10.3390/biomedicines9040333
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role and Utility of MicroRNAs in Indolent B-Cell Non-Hodgkin Lymphomas

Abstract: Normal B-cell development is a tightly regulated complex procedure, the deregulation of which can lead to lymphomagenesis. One common group of blood cancers is the B-cell non-Hodgkin lymphomas (NHLs), which can be categorized according to the proliferation and spread rate of cancer cells into indolent and aggressive ones. The most frequent indolent B-cell NHLs are follicular lymphoma and marginal zone lymphoma. MicroRNAs (miRNAs) are small non-coding RNAs that can greatly influence protein expression. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 169 publications
0
13
0
Order By: Relevance
“…Studies have highlighted the putative role of microRNA in the pathogenesis of these lymphomas and showed that the SMZL deregulates the expression of 51 miRNAs [ 26 , 42 , 43 , 44 ]. According to Arribas et al, the most overexpressed miRNAs seem to be “miR-155, miR-21, miR-34a, miR-193b and miR-100, while the most repressed miRNAs are miR-377, miR-27b, miR-145, miR-376a and miR-424” [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have highlighted the putative role of microRNA in the pathogenesis of these lymphomas and showed that the SMZL deregulates the expression of 51 miRNAs [ 26 , 42 , 43 , 44 ]. According to Arribas et al, the most overexpressed miRNAs seem to be “miR-155, miR-21, miR-34a, miR-193b and miR-100, while the most repressed miRNAs are miR-377, miR-27b, miR-145, miR-376a and miR-424” [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in HCV-associated SMZLs, antiviral treatment (protease inhibitors, NS5A, or NS5B inhibitors) results in a marked reduction of lymphocytosis and splenomegaly. However, the underlying mechanisms are poorly understood [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, part of cancer transcriptomic data originates from preclinical research employing cell lines and mouse models. Despite the undeniable value of these data, molecular differences between these models and patient tumors call for caution in extending results to the human system [ 128 , 129 ]. Therefore, approaches aiming at delineating the similarities and differences between preclinical and clinical transcriptomes are required for an effective application of AI to improve the patient’s quality of life [ 130 , 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential molecular biomarkers for early diagnosis and prognostic stratification include circulating microRNAs (miRNAs). Nowadays, there is no doubt that miRNAs play a crucial role in both pathological and physiological processes via post-transcriptional regulation of gene expression [9][10][11]. A single miRNA may target hundreds of messenger RNAs (mRNAs) [12].…”
Section: Introductionmentioning
confidence: 99%